Using Laboratory Investigations to Aid the Identification of Small Aromatic Molecules in Water-Containing Astrophysical Ices - Salter, Tara L.; Stubbing, James W.; Brigham, Lorna; Brown, Wendy A. (Frontiers in Astronomy and Space Sciences, 2021)
Monocyclic aromatic hydrocarbons such as benzene, toluene and xylene are thought to play an important role as precursors to the formation of polycyclic aromatic hydrocarbons (PAHs) and their methylated counterparts in a range of astrophysical environments. Benzene has been detected in two carbon rich objects and models have predicted that it could also be present in the interstellar medium (ISM). It has hence been speculated that small aromatic molecules are present in molecular clouds in the ISM, although they have not been detected to date. If they are present in the ISM, they are likely to exist in water-ice dominated icy mantles on the surface of dust grains. We present a laboratory study of benzene, toluene and two xylene isomers (ortho- and para-xylene) in the presence of water ice on a carbonaceous model dust grain surface (highly oriented pyrolytic graphite, HOPG). Temperature programmed desorption (TPD) shows how the desorption of the molecules is affected by the presence of water ice. The importance of these data for astrophysical situations is demonstrated by the use of TPD-derived kinetic parameters to generate a simple model of desorption in dense molecular clouds on an astrophysical timescale. Since benzene, toluene and xylene have not been detected in water-dominated icy mantles to date, desorption has been simulated in a range of different water-containing environments to show the different behaviour expected depending on ice composition. The simulations demonstrate how future observations of aromatic molecules in dense molecular clouds at known temperatures could reveal which environments the molecules are in. Data from these experiments are also used to predict the behaviour of other, larger, aromatic molecules such as PAHs. Reflection absorption infrared spectroscopy (RAIRS) is also used to record the infrared spectra of the small molecules in different water ice configurations. These spectra can be used to aid identification of these icy aromatics in future observations, such as those that will be possible with the James Webb Space Telescope (JWST). In all cases, spectra of mixed ices consisting of the aromatic molecule and amorphous water ice show evidence of interactions between the water ice and the aromatic species.